Kebijakan Kepala Sekolah Dalam Meningkatkan Presetasi Siswa Kelas 6 Di SD Negeri Tenau Kupang - Ariyanto Letik; Yossia Lende; Raymundus Nonatus Mau (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research aims to describe and analyze the principal's policy in improving the achievement of class VI students at Tenau Kupang Elementary School. Using a descriptive qualitative approach, data was collected through interviews, observation and documentation. The research results show that the main aim of the principal's policy is to produce graduates who are able to compete at the secondary education level, have high values ​​and dedication, and are ready to enter the world of work. Challenges faced include limited access to technology and school infrastructure. The strategies implemented include disseminating policies to teachers, parents and students, effective communication, evaluating teacher performance, and efforts to overcome educational inequalities. In conclusion, the success of school principal policies in improving student achievement depends on effective collaboration between the school, parents and community, as well as the ability to overcome internal and external challenges.